Analysis of the Effect of Operational Costs on the Profitability of the Tirta Dharma Regional Drinking Water Company, Belu Regency - Syarin Adisti Vanadis Masorong; Petrus Emanuel De Rozari; Aldarine Molidya (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to identify and analyze operating costs to increase the profits of the Tirta Dharma Drinking Water Regional Company in Belu Regency. This study employs quantitative descriptive research, specifically analyzing operational costs as variable X by calculating the ratio of operating expenses to operating income (BOPO) and assessing profitability ratios as variable Y by calculating Net Profit Margin, Return On Asset, and Equity. Data were collected through observation, interviews, and documentation methods. The study findings suggest that the profit gained by PDAM Tirta Dharma Belu Regency through Net Profit Margin (NPM) calculation has been fluctuating. This implies that the net earnings from sales have not been maximized. Additionally, the calculation of Return on Asset (ROA) reveals the fluctuating profit obtained by the company. Moreover, the computation of Return on Equity (ROE) reveals that PDAM Tirta Dharma Belu Regency has also faced fluctuations. This suggests that the company could not utilize capital assistance to its full potential. The reduction in profitability at the Regional Drinking Water Company of Belu Regency can be attributed to suboptimal fund management and excessive operating expenses. In other words, despite the company's ability to generate profits from its business activities, it could not lower the high operating costs. As a result, the operating costs are not optimal, making it difficult to enhance the company's profitability efficiently